Profil Prestasi Atlet Renang Grup 3 Kota Semarang Tingkat Jawa Tengah Tahun 2019 - Klarita dewi, Dinda Putri; Sungkowo, Sungkowo; Rahayu, Kaswarganti; Setiawan, Tritunggal (Universitas Negeri Semarang, 2020)
This study examines the performance profile of Semarang City swimming athletes who are in group 3 (12-13 years). Focus on how the development profile of Semarang City Group 3 athlete swimming achievements in 2019? The purpose of this study was to determine the profile of the achievements of group 3 swimming athletes in Semarang City, Central Java Level 2019. This type of research is descriptive. The population in this study were group 3 swimmers, one male and four female, interview data collection methods and documentation via the JatengFast Web. The data analysis technique uses descriptive qualitative. Conclusions in this study, there was an increase and decrease in the time record of Semarang 3 group swimming athletes starting from KRAP INTANPARI Open in 2019, Central Java Kejurprov - 2019 Batang Regent Cup, Semarang City POPDA, POPDA PROVINCE and in the KRAPPROV race in Jepara Regent 2019 Cup.